2002
DOI: 10.1159/000057701
|View full text |Cite
|
Sign up to set email alerts
|

Serum Folate Levels and Subsequent Adverse Cerebrovascular Outcomes in Elderly Persons

Abstract: Recent epidemiologic studies have shown an association between low serum folate levels and risk of vascular disease, including stroke and various types of vascular cognitive impairment. We examined data from the Canadian Study of Health and Aging (CSHA), a population-based, prospective 5-year investigation of the epidemiology of dementia among Canadians aged 65+ years. The risk of an adverse cerebrovascular event (including vascular dementia, vascular cognitive impairment, or fatal stroke) during follow-up, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 52 publications
1
40
1
Order By: Relevance
“…39 More recently, a randomized controlled trial failed to find a difference in recurrence of stroke between low-and high-dose vitamin intake (folate, vitamin B6, and vitamin B12) through lowering of homocysteine levels. 40 Most of the studies that have examined the direct relationship between folate and stroke were based on serum folate levels [17][18][19]34 and only 2 recent cohort studies assessed the intake of folate in relation to the risk of stroke. 20,41 However, serum and dietary folate are well correlated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39 More recently, a randomized controlled trial failed to find a difference in recurrence of stroke between low-and high-dose vitamin intake (folate, vitamin B6, and vitamin B12) through lowering of homocysteine levels. 40 Most of the studies that have examined the direct relationship between folate and stroke were based on serum folate levels [17][18][19]34 and only 2 recent cohort studies assessed the intake of folate in relation to the risk of stroke. 20,41 However, serum and dietary folate are well correlated.…”
Section: Discussionmentioning
confidence: 99%
“…The Bronx aging cohort study found no association between serum folate levels and incidence of stroke. 17 In the Canadian Study of Health and Aging, Maxwell et al 19 found an increased risk of cerebrovascular events (including vascular dementia, vascular cognitive impairment, and fatal stroke) among subjects in the lowest folate quartile compared with the highest quartile (odds ratio [OR]: 2.42; 95% CI: 1.04 to 5.61). After further follow-up of NHANES I, Bazzano et al 20 used dietary intake of folate instead of serum folate levels and followed-up 9764 men and women aged 25 to 75 years for an average of 19 years, with 926 incident cases documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-three studies examined the relationship between mean folate level and cognitive function or Parkinson's disease [12-14, 17-20, 22, 24-27, 29-33, 36, 39-43]; 9 examined the prevalence of folate deficiency [11,21,23,24,26,27,31,44,46]; and 11 assessed the risk of Alzheimer's disease, dementia, and cognitive impairment according to folate levels [10-12, 22, 23, 25, 29, 32, 41, 44]. The folate levels were assessed in the red blood cells, plasma, serum, cerebrospinal fluid, and blood.…”
Section: Folate Blood Levelsmentioning
confidence: 99%
“…Six other studies that examined the odds of Alzheimer's disease in relation to high versus low levels of folate reported increased odds but no significant association. Maxwell et al [44] examined the risk of adverse health outcomes, including cognitive decline, associated with quartile of folate level during a 5-year follow-up. This study reported that subjects with the lowest folate levels were at greater risk for significant cognitive decline.…”
Section: Folate Blood Levelsmentioning
confidence: 99%